Comparative and competitive advantages of nutmeg farming in two regions in Maluku Province, Indonesia - Tienni Simanjorang; Irham; Lestari Rahayu Waluyati; Jangkung Handoyo Mulyo (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Simanjorang TM, Irham, Waluyati LR, Mulyo JH. 2020. Comparative and competitive advantages of nutmeg farming in two regions in Maluku Province, Indonesia. Biodiversitas 21:  1165-1173. Comparative and competitive advantage is one of the main keys to the development of nutmeg farming in Maluku Province to deal with globalization and market liberalization. Consequently, assessments are needed in developing efforts to improve the comparative and competitive advantage of nutmeg farming. The purposes of this study are to find out the private and social benefits of nutmeg farming, to find out the comparative and competitive advantages of nutmeg farming, and to compare the level of competitiveness of small-scale nutmeg farming in two regions in Maluku Province, Indonesia, namely the Ambon Island region and the Banda Islands region. Data were collected using direct interview techniques to smallholder nutmeg farmers selected purposively. The data was then analyzed using the Policy Analysis Matrix (PAM) and the t-independent test of difference. The results show that nutmeg farming in the Banda Islands region has higher private and social benefits than in the Ambon Island region, because the nutmeg farming system in Banda Islands region is carried out intensively and the price of nutmeg farms received by farmers is higher, The competitive and comparative advantage of nutmeg farming in the Banda Islands region is higher than in the Ambon Island region. All these results suggest that in general nutmeg farming in the Banda Islands region is more competitive than in the Ambon Island region.